Measurement and evaluation of supply chain business process models - Orlovskyi, D. L.; Kopp, A. M.; Laktionov, S. Y. (Одеська національна академія харчових технологій, 2020)
This paper considers the supply chain management and its most remarkable business process reference model SCOR. This model is considered as a hierarchical system of business process definitions amended with respective indicators and practices. Supply chains are tend to be described using business process modeling notations such as BPMN, while design flaws could cause supply chain defects and, hence, monetary losses and time delays. Therefore, this study is aims to improve the quality of supply chain business process models in order to ensure correct execution of the supply chain activities.
Keywords: business-process; supply chain; reference model SCOR; calculated measures; threshold values; efficiency levels